Paradoxes in practices of inclusion in physical education - van Doodewaard, Corina; Knoppers, Annelies (Frontiers in Sports and Active Living, 2022)
The purpose of this paper was to explore how high school PE teachers create norms for inclusion based on gender as it intersected with ethnicity, ability, and effort.